Different anti-CD21 antibodies can be used to discriminate developmentally and functionally different subsets of B lymphocytes in circulation of pigs - Sinkora, Marek; Stepanova, Katerina; Sinkorova, Jana (Developmental and comparative immunology, 2013)
Monoclonal antibodies IAH-CC51, BB6-11C9.6 and B-Ly4 are routinely used to detect CD21 orthologue on the surface of porcine B lymphocytes. Cross-reactive studies show that IAH-CC51 and B-Ly4 recognize only a portion of B cells that are positive for pan-specific BB6-11C9.6. This indicates that CD21 is always present on all mature B cells but can be expressed in at least two differential forms, and these were assigned as CD21(a) and CD21(b). We used IAH-CC51 together with anti-CD2 to define four subpopulations of B cells. Ontogenetic and in vitro culture studies, analysis of cell size, expression of CD11b and class-switched phenotype together with measurement of proliferation and cell death, revealed that these subsets represent distinct populations. Phenotypic and functional features collectively suggest that CD21(b+) B cells are less mature than CD21(b-). The present work is the first to show that distinct subsets of mature B cells can express differential forms of CD21.
Keywords: Epitopes; apoptóza; monoklonální protilátky; B-Lymphocyte Subsets; Animals; Swine; receptory komplementu 3d; Cells, Cultured; Receptors, Complement 3d; podskupiny B-lymfocytů; epitopy; kultivované buňky; prasata; Antibodies, Monoclonal; zvířata; Apoptosis